Dhikr Therapy Can Improve Muscle Strength In Non-Hemorrhagic Stroke Patients - Setiyawan Setiyawan; Dewi Yuni Anggraeni; Annisa Cindy Nurul Afny ((JKG) Jurnal Keperawatan Global, 2021)
Background: Non-hemorrhagic stroke is a disease that occurs due to a blockage in certain brain blood vessels. Therefore, the brain area is not supplied with energy and oxygen so that the brain tissue does not function. The problem that occurs in non-hemorrhagic strokes is the weakness of the limbs and facial muscles. Non-pharmacological therapy for non-hemorrhagic stroke sufferers is dhikr therapy. Dhikr therapy relies on feelings and heart to calm the soul and increase muscle strength. This study aims to determine the effect of dhikr therapy on muscle strength in non-hemorrhagic stroke patients Methods: This study used a quasi-experimental research design with pre-and post-test with control group. Non-probability sampling was used to determine the sample, which consisted of 54 respondents: 27 in the treatment group with ROM therapy, dhikr and 27 in the control group with ROM therapy. Manual Muscle Testing (MMT) Instrument is used to measure muscle strength. The data were analyzed using an independent T-test Results: There is an effect of dhikr therapy on muscle strength after implementing the therapy in the intervention and control groups with a p-value of the right upper extremity of 0.000, p-value of the left upper extremity of 0.008, p-value of the right lower extremity of 0.007 and p-value of the left lower extremity of 0.007 Conclusion: The results of this study indicate that dhikr therapy can improve muscle strength in non-hemorrhagic stroke patients at the Sibela Community Health Center of Surakarta